Imam al-Bazzars approach to deal with Singularity of Hadith in later stage of chain of narrators: الأحاديث التي ذكر فيها الإمام البزّار التفرّد وهي معلولة لكون الراوي من الطبقات المتأخرة. (مسند أنس رضي الله عنه نموذجا) - Akram, Reema (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Tafarrud of a prophetic tradition means reporting of hadith by a single narrator at some stage of chain of narrators. Tafarrud is not considered to be a defect itself, but it may indicate towards an error in reporting the hadith. Therefore, judgement on such traditions is based on certain factors which are discussed in the sciences of hadith and its hidden defects. One of the factors that cause doubt in the authenticity of such unique traditions is tafarrud in later stage of chain of narrators. This paper analyzes approach of Imam Al-Bazzar in dealing with tafarrud of prophetic traditions in later stage of chain of narrators and its effects on judgement of hadith.